Establishment Differences Odontoblast Like Cell On Reversible Pulpitis With MTA And Nano Hydroxyapatite Sell Duck Eggs (In Vivo Study) - Rio Susilo Putra; Cahyani Cahyani; Nur Ariska Nugrahani; Aprilia Yuanita Anwaristi (Sean Institute, 2023)
Reversible pulpitis is a pathological condition of the pulp which can return to normal when the etiology of the condition is removed. Reversible pulpitis can be treated with pulp capping treatments to stimulate formation odontoblast like cell. Alternative materials are mineral trioxide aggregate (MTA), Biodentine and Nano hydroxyapatite (nHA) from duck shells. Purpose: to find out whether there is a difference in the number of formations odontoblast like cell in reversible pulpitis with MTA and nano hydroxyapatite duck egg shell. in vivo laboratory experiment test only control design with the independent variables, namely MTA and Nano Hydroxyapatite duck eggs and the dependent variable, namely the difference in the number of formation Odontoblast like-cell. The sample used was the RA right molar tooth of a male Sprague Dawley rat. Results: The results obtained were (p value 0.001), there was a significant difference between the average number of formations odontoblast like cell in each treatment group and control group. Administration of Nano hydroxyapatite medicament from duck egg shells and MTA medicament in the treatment of pulp caps can increase the formation of odontoblast like cell in reversible pulpitis.